Paradigma Sosial Kristiani bagi Keluarga Kristiani menurut Lisa Sowle Cahill - Andreas Yanulian Tri Utomo Hadi (Jurnal Teologi (Journal of Theology), 2018)
In Family: A Christian Social Perspective, Lisa Sowle Cahill explained how is the paradigm shift of Christian family before the danger of individualism from the phenomenon of nuclear family in North America towards the end of the 20th century. The phenomenon of the nuclear family coincides with widening economic gap and increasing gender discrimination in the society. Cahill speaks about the Christian family as Domestic Church. Christian family is not merely nuclear family that focuses only on the welfare of its family members (bonum coniugum). The Christian family is a socially transformative family for the realization of Christian ideals : love for humanity for common good. Cahill states that the Christian family not only includes the bonds of relatives, but also establishes a close communion with various parties as a bond of solidarity to seek common good. Amoris Laetitia, an apostolic exhortation written by Pope Francis, is the Church's response to the current family situation. Pope Francis has similar ideas with Cahill. He said that family as Domestic Church, called every member of the family to be involved in the world and dared to meet their fellow human beings as sisters and brothers, and fight for justice.